Closing the gap: efficacy of a tablet intervention to support the development of early mathematical skills in UK primary school children - Outhwaite, Laura A.; Gulliford, Anthea; Pitchford, Nicola J. (Elsevier, 2017)
The efficacy of a hand-held tablet technology intervention with learner-centred interactive software aimed at supporting the development of early maths skills was evaluated in four studies conducted in three UK primary schools. Immediate and sustained gains in mathematics were determined by comparing maths performance before, immediately after, and 5-months after the intervention. The impact of the child's first language, socio-economic status and basic cognitive skills (non-verbal intelligence, memory, processing speed and receptive vocabulary) on learning gains was also explored. In total, 133 pupils aged 4–7 years took part. Class teachers implemented the maths intervention for a specified period of time. Results showed significant immediate and sustained learning gains following the intervention, particularly for children identified as low-achievers. No significant effect of child's first language or socio-economic status was found but children with weaker memory skills demonstrated stronger learning gains. Overall, these findings indicate that tablet technology can provide a form of individualised effective support for early maths development, when software is age appropriate and grounded in a well-designed curriculum. Apps that incorporate repetitive and interactive features might help to reduce cognitive task demands, which could be particularly beneficial to low-achievers and could help to close the gap in early maths attainment from the start of primary school.